2018
DOI: 10.1016/j.omtm.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Universal Method for the Purification of Recombinant AAV Vectors of Differing Serotypes

Abstract: The generation of clinical good manufacturing practices (GMP)-grade adeno-associated virus (AAV) vectors requires purification strategies that support the generation of vectors of high purity, and that exhibit a good safety and efficacy profile. To date, most reported purification schemas are serotype dependent, requiring method development for each AAV gene therapy product. Here, we describe a platform purification process that is compatible with the purification of multiple AAV serotypes. The method generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 26 publications
4
112
1
1
Order By: Relevance
“…Purification of the vector was performed by column chromatography as previously described. 46 The vector preparation was substantially free of contaminants, as assessed by SDS-PAGE analysis with SYPRO staining; additionally the fractional content of empty capsids in the vector preparation was low at 13%, as determined by analytical ultracentrifugation ( Figure S4). 47…”
Section: Aav Vector Productionmentioning
confidence: 99%
“…Purification of the vector was performed by column chromatography as previously described. 46 The vector preparation was substantially free of contaminants, as assessed by SDS-PAGE analysis with SYPRO staining; additionally the fractional content of empty capsids in the vector preparation was low at 13%, as determined by analytical ultracentrifugation ( Figure S4). 47…”
Section: Aav Vector Productionmentioning
confidence: 99%
“…Triton X-100 is a commonly used detergent that has shown to be effective yet inexpensive. Use of detergents is concentration and time dependent, with reported concentrations of Triton X-100 between 0.1% (2 hr and 37°C; Nass et al, 2018) it poses a potential concern for the downstream impact on chromatographic unit operations exists. The use of acidic buffers for cell lysis, such as citrate at pH 4.2, has also been explored (Kimura et al, 2019;Shuhei Sakamoto et al, 2018) and could prove an alternative to detergents that could mitigate the impact on downstream unit operations as well as the need to show clearance of the additive.…”
Section: Harvest and Clarification Of Aav Cell Culturementioning
confidence: 99%
“…The first commercially available camelid resin was AVB Sephar-ose™ High Performance (GE Healthcare Life Sciences, 2016) which combines an agarose (Sepharose) base bead with a ligand that was isolated from llamas naturally exposed to wild-type AAV (Nass et al, 2018). As such, during development of this resin it was found that the antibody fragment selected displayed high affinity for AAV vectors with capsids of serotypes 1, 2, 3, and 5 (GE Healthcare Life Sciences, 2016).…”
Section: Purification Of Aav Vectors Through Capture Chromatographymentioning
confidence: 99%
“…However, the differences were too small to clearly distinguish between full and empty AAVs in a complex sample mixture. For this purpose, other analytical methods can be used such as anion-exchange-chromatography, 33,34 analytical ultracentrifugation, 35,36 and transmission-or cryo-electron microscopy. 37 In summary, DSF offers a rapid, cost-effective, and robust method for AAV serotype identification due to their unique thermal stability profiles in the commonly utilized formulation and storage buffers and detergents.…”
Section: Discussionmentioning
confidence: 99%